2013
DOI: 10.1016/j.phytochem.2012.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the phenylacetic acid metabolic complex by quinic acid alters the disease-causing activity of Rhizoctonia solani on tomato

Abstract: The metabolic control of plant growth regulator production by the plant pathogenic fungus Rhizoctonia solani Kühn (teleomorph=Thanatephorus cucumeris (A.B. Frank) Donk) and consequences associated with the parasitic and saprobic activity of the fungus were investigated. Fourteen genetically distinct isolates of the fungus belonging to anastomosis groups (AG) AG-3, AG-4, and AG-1-IA were grown on Vogel's minimal medium N with and without the addition of a 25 mM quinic acid (QA) source of carbon. The effect of Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…The disease syndrome may evolve rapidly to a fatal consequence in formerly symptomless host (damping off and wilting). Our data support the assumption of crucial role of mycotoxins in evolution of disease syndrome [9,22]. Like to series of host plants [8,10,31] the strain dependent response of A. thaliana clones to Rhizoctonia was demonstrated in our experiments as well.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The disease syndrome may evolve rapidly to a fatal consequence in formerly symptomless host (damping off and wilting). Our data support the assumption of crucial role of mycotoxins in evolution of disease syndrome [9,22]. Like to series of host plants [8,10,31] the strain dependent response of A. thaliana clones to Rhizoctonia was demonstrated in our experiments as well.…”
Section: Discussionsupporting
confidence: 88%
“…Their relationship may change from symbiosis (as in various orchids) to parasitism. The stunted growth can be most frequently observed, which might be related to the effect of Rhizoctonia toxins although few evident experimental proof has been demonstrated yet [9]. Presence of parasitic hyphae can also be commonly seen even in symptomless tissues, and in normal conditions does not cause visible disease symptoms either in phyllosphere or in roots.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that R. solani also produces phenyl acetic acid and its derivatives (Bartz et al, 2013 ), a phenolic compound, and a carbohydrate as phytotoxins that supported the broad host range and diversity within the R. solani species. Xu et al ( 2015 ) identified eight compounds from fermentation broth of R. solani , from which m -hydroxymethylphenyl pentanoate, (Z)-3-methylpent-2-en-1,5-dioic acid and 3-methoxyfuran-2-carboxylic acid showed phytotoxicity in vitro .…”
Section: Phytotoxins Phytoalexins and Special Smsmentioning
confidence: 85%
“…Following the method of Bartz (2010), potato dextrose (PD) broth medium was balanced to pH 2.5 (that was helpful for pathogenesis), and autoclaved at 121°C and at approximately 16 psig for 45 min, and then amended with a filter-sterilized aqueous solution of MTPA standardized to pH 2.5. Amended media were adjusted to various concentrations of MTPA: 1.0, 2.0, 4.0 and 8.0 mM for use.…”
Section: Methodsmentioning
confidence: 99%